Effects of mobile gaming patterns on learning outcomes: a literature review. (1st February 2013) - Schmitz, Birgit; Klemke, Roland; Specht, Marcus
Within the past decade, a growing number of educational scientists have started to recognise the multifaceted potential that mobile learning games have as a tool for learning and teaching. This paper presents a review of current research on the topic to better understand game mechanisms with regard to learning outcomes. The purpose of this paper is twofold. First, we introduce a framework of analysis which is based on previous work on game design patterns for mobile games and on learning outcomes. The framework focuses on two aspects, motivation and knowledge gain. Second, we present a set of patterns which we identified in the literature and that positively influence these two aspects. Our results support the general assumption that mobile learning games have potential to enhance motivation. It reveals that game mechnisms such as Collaborative Actions or Augmented Reality provide incentive to get engaged with learning and/or a certain topic. With regard to knowledge gain, results are less comprehensive.